Dystonia: diagnosis and management. (18th August 2018) - Albanese, A.; Di Giovanni, M.; Lalli, S.
Abstract : Clinical practice in dystonia has greatly evolved in recent years; a synthetic review on patient management is provided here. Dystonia is a movement disorder characterized by sustained or intermittent muscle contractions causing abnormal, often repetitive, movements, postures or both. A recent classification has innovated clinical practice and serves as guidance for clinical assessment: Axis I describes clinical features, whereas Axis II indicates etiology. Dystonia presents with different syndromic aggregations with varied somatic involvement and some common features. There are five recognizable physical signs of dystonia: two main signs (dystonic postures and movements) and three additional signs ( gestes antagonistes or tricks, mirror dystonia and overflow dystonia). There is still no validation of diagnostic criteria for the different dystonia syndromes, and many cases with mild phenomenology remain undiagnosed. Patients with dystonia also present non‐motor features that are variably combined with the movement disorder. The features of the most common inherited and acquired dystonia syndromes are reviewed here. There is clear evidence of genetic–environmental interaction in the determinism of dystonia. The diagnostic process is guided by clinical examination and based on specific laboratory examinations. Symptomatic treatments are available for dystonia: botulinum neurotoxin injections are the primary choice for most focal dystonia syndromes; deep brain stimulation is useful in some generalized and non‐generalized syndromes. Additional treatment strategies are currently being assessed.